Glycaemic Control after Metformin Discontinuation in Diabetic Patients with a Declining Renal Function - Theresa Leyco; Davin Ryanputra; Ray Peh; Alexphil Ponce; Chin Meng Khoo (Journal of Diabetes Research)
Metformin is contraindicated in diabetic patients with declining renal function. This study examined the glycaemic control in diabetic patients with chronic kidney disease when metformin was discontinued. This was a retrospective study. We screened 2032 diabetic patients who attended the Diabetes Clinic at a tertiary hospital between 1 September 2014 and 30 September 2015. We analyzed the data on 69 patients whom metformin was discontinued due to declining renal function and had a complete 6-month follow-up. There was no significant difference in the HbA1c and body weight at 6-month follow-up compared to baseline after metformin discontinuation. The eGFR was significantly lower at 6-month follow-up compared to baseline. Upon metformin discontinuation, the majority of patients had their diabetes medication uptitrated (in particular insulin or sulphonylurea). Patients with an improved glycaemia at 6-month follow-up had further declined in eGFR compared to patients with worsened glycaemia. 17% of the study patients experienced hypoglycaemia. Upon metformin discontinuation, glycaemic control could be optimised with uptitration but should be balanced against the risk of hypoglycaemia. Further improvement in the glycaemic control might indicate further deterioration in the renal function.